CAN COST OF PHARMACOLOGICAL THROMBOLYTIC THERAPY BE A MEDICATION MANAGEMENT STRATEGY FOR ACUTE CORONARY SYNDROME? - Kumar, Vinod; Panda, Bijoy Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objectives: In Indian health-care system with delayed access to a minimum number of catheter laboratories and rarity of insurance benefits, prehospital and in-hospital thrombolytic has become the choice for patients with acute coronary syndrome (ACS), where many patients bear the economic burden of pharmacological thrombolytic. The present study was carried out to evaluate the pattern of prescribing of pharmacological thrombolytic agents in hospitalized ACS patients and associated cost burden. Methods: A prospective observational cohort study of prescription was conducted for in-patient admitted to intensive care unit for thrombolytic and antithrombotic drug utilization pattern. The direct cost analysis was performed from patient's perspective where a direct cost was calculated using pharmacy bills. All other cost was assumed to be same. Results: Data of 288 patients were collected from which 108 (37.5%) patients were ST-elevation myocardial infarction (STEMI) and 180 (62.5%) patients were non-STEMI. The mean number of drugs prescribed was 11±2 which constitutes a mean of 3.1±0.7 reperfusion drugs. 59% of patients were prescribed with enoxaparin (0.6 ml/seconds route) for the mean duration of 4 days. The average prescription cost for ACS admission was around Rs.7159.5±5137.2 (Rs.1101-Rs.22202). The average cost of pharmacological thrombolytic therapy was Rs.4557±3468.3 (Rs. 23-Rs.12542). The mean cost of pharmacological thrombolytic therapy was found to be 63% of the total direct cost of drugs borne by the patient. The cost of therapy was positively correlated with duration of stay (p=0.000) and insignificantly correlated with a number of drugs. Conclusion: Antiplatelets were the most preferred followed by anticoagulants. The mean number of drugs per encounter was high but was rational as per standard guidelines. The mean cost for pharmacological reperfusion therapy was found to be more than half of mean prescription cost for the management of ACS. Keywords: Acute coronary syndrome, Thrombolytic therapy, Cost, Medication management.